Mental Health Conditions of Italian Healthcare Professionals during the COVID‐19 Disease Outbreak. Issue 4 (5th October 2020) - Bettinsoli, Maria Laura; Di Riso, Daniela; Napier, Jaime L.; Moretti, Lorenzo; Bettinsoli, Pierfrancesco; Delmedico, Michelangelo; Piazzolla, Andrea; Moretti, Biagio
Abstract : Background: The COVID‐19 pandemic in Italy represents a unique threat in terms of psychological distress. This cross‐sectional study aims to investigate the psychological health of Italian healthcare professionals during the COVID‐19 outbreak. We assessed participants' current psychological distress and coping strategies in the midst of the COVID outbreak (March–April 2020), and also asked them to retrospectively report how they remember feeling before the COVID‐19 outbreak (December 2019). We examined associations between psychological distress and coping strategies with mental health and infection perceptions. Methods: Self‐administered questionnaires were distributed online to healthcare professionals ( N  = 580) residing in different Italian regions from 26 March to 9 April 2020. The questionnaire measured changes in psychological states, coping strategies, and demographic variables testing variations in mental health and infection risk perception among Italian healthcare workers. Results: Overall, approximately 33.5 per cent of healthcare professionals in our sample meet the threshold for psychiatric morbidity. Participants perceive their current psychological health to be worse during the COVID‐19 emergency outbreak as compared to before the outbreak, and this was especially true among women. Conclusions: Both immediate and long‐term monitoring psychological assistance services for healthcare workers should be implemented by national institutions to re‐establish the psychological well‐being and enhance the self‐confidence and resilience of hospital personnel.